2012
DOI: 10.1371/journal.pone.0036098
|View full text |Cite
|
Sign up to set email alerts
|

NT2 Derived Neuronal and Astrocytic Network Signalling

Abstract: A major focus of stem cell research is the generation of neurons that may then be implanted to treat neurodegenerative diseases. However, a picture is emerging where astrocytes are partners to neurons in sustaining and modulating brain function. We therefore investigated the functional properties of NT2 derived astrocytes and neurons using electrophysiological and calcium imaging approaches. NT2 neurons (NT2Ns) expressed sodium dependent action potentials, as well as responses to depolarisation and the neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 46 publications
2
57
0
Order By: Relevance
“…; Hill et al . ; Pirttimaki & Parri, ). Thus, astrocytes are probably a significant component of the molecular, synaptic and cognitive consequences of aberrant Aβ accumulation in AD pathogenesis that have largely been overlooked (Teaktong et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Hill et al . ; Pirttimaki & Parri, ). Thus, astrocytes are probably a significant component of the molecular, synaptic and cognitive consequences of aberrant Aβ accumulation in AD pathogenesis that have largely been overlooked (Teaktong et al .…”
Section: Discussionmentioning
confidence: 98%
“…We and others recently showed that a key mediator of astrocyte α7 nAChR function is Aβ, a ubiquitously expressed signalling peptide and putative toxic trigger for AD (Parri & Dineley, 2010;Pirttimaki et al 2013;Talantova et al 2013;Lee et al 2014). Astrocytes play a critical role in synaptic transmission, plasticity and memory formation through the release of chemical transmitters (gliotransmitters) such as glutamate (Pirttimaki et al 2011;Hill et al 2012;Pirttimaki & Parri, 2012). Thus, astrocytes are probably a significant component of the molecular, synaptic and cognitive consequences of aberrant Aβ accumulation in AD pathogenesis that have largely been overlooked (Teaktong et al 2003); these proof-of-concept studies position us to specifically address their role in AD initiation and progression in preclinical models as well as several other cell-type-specific roles (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…21 We have recently demonstrated that NT2.D1 cell-derived neuron and astrocyte (NT2.N/A) networks can communicate and so have the potential to interact with each other as observed in vivo. 22 If this model is to be applied to the investigation of human neuronal function, it is also essential that the metabolic relationship is sufficiently representative of functional reality.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will identify the temporal nature of these changes in order to fully understand the mechanism of action of these compounds. In addition, we will also determine the functional effects of these compounds on neurons and astrocytes derived from these cultures [39]. Following further validation with a larger range of toxins this approach may prove useful for identifying potential developmental neurotoxins as part of a battery of tests for regulatory screening processes.…”
Section: Discussionmentioning
confidence: 99%